A cross-country study on manipulations in financial statements of listed companies: Evidence from Asia. Issue 4 (2nd October 2017) - Hasan, Md Shamimul; Omar, Normah; Barnes, Paul; Handley-Schachler, Morrison
Abstract : Purpose: The purpose of this study is threefold: first, to detect trends in financial statement manipulation; second, to measure the level of manipulation and to measure the variation in manipulation between countries; and, third, to identify widely used techniques in financial statements manipulation. Design/methodology/approach: This study uses financial data of listed companies from Asia, namely, Japan, Singapore, Malaysia, Indonesia, Thailand, Hong Kong and China. The study adopts financial ratios, financial forensic tool, dichotomous approach and statistical tools to analyze the data (84, 000 observations) over a period of four years from 2010 to 2013. Findings: The results show that 34 per cent of sample companies in selected Asian countries are involved in the manipulation of financial statements; the average level of manipulation (overall manipulation index) is 72 per cent; and there is a significant difference between countries at 5 per cent level. The study also identifies four most commonly used techniques, namely: days' sales in receivable (DSRI), depreciation (DEPI), assets quality (AQI) and total accruals to total assets (TATA). Research limitations/implications: Although this study found a significant national difference between countries in terms of practicing manipulation in financial statements, it did not address the issue of why some countries have higher level of manipulation and greater fluctuations in manipulation than others. Further study could be conducted to look for the reasons on these issues. Practical implications: Investors and other stakeholders are advised to judge the manipulation in financial statements before fixing up for investment. At least they should examine Sales, Accounts Receivable, Depreciation, Value of Fixed Assets and Accruals data before accepting the financial statement in good faith. Social implications: The trend of manipulation in financial statements is increasing day by day and that is why it needs to prevent to protect our society from white collar crime. The cost of white collar crime is much higher and key executives are making money at the expense of investors and other stakeholders. This kind of study creates awareness among stakeholders about the manipulation as well as provides techniques to examine the faithfulness of financial statements. Then, managers will not overstate or understate either revenues or expenses easily, as it can damage the goodwill. Originality/value: This is the first study of its kind addressing measurement of manipulation score, overall manipulation index (OMI) and identification of widely used variables of manipulation in financial statements are new contributions towards existing literature of earnings manipulation.